Women Artists in the British and Ukrainian Literature at the Turn of the 19th – 20th Century: D. H. Lawrence’s Women in Love and O. Kobylianska’s Valse Mélancolique - Devdiuk, Ivanna Vasylivna; Nisevych, Svitlana I. (Journal of History Culture and Art Research, 2020)
The article analyzes the peculiarities of women-artists’ portrayal in the texts Women in Love by D. H. Lawrence and Valse Mélancolique by O. Kobylianska in the light of feminism and intermediality. Its relevance is conditioned by a new wave of interest in feminist interpretation, the comparative study of the relationship between visual art-literature and the opportunity to expand the line of the research of English-Ukrainian literary cross-cultural relationships. The purpose of this article is to determine the similarities and differences in the images of women artists. In order to achieve this objective, we used feminist approaches, elements of intermedial and contextual analyzes, as well as biographical and typological methods. The research showed that the correspondences in the images of women-artists are obvious at different levels: the importance of art in the life of the protagonists, criticism of patriarchal society with all its conventions towards women, focus on strong personalities of women-artists, elements of visual art incorporated in the literary works. Despite the different socio-cultural situation in Britain and Ukraine at the turn of the 19th –20th century, the prose works of D. H. Lawrence and O. Kobylianska proved the authors’ common interpretation of women-artists images, which correlate with the modernist principles of a free choice and self-expression.